High-strength high-modulus para-aramid fiber and preparation method thereof

By mixing polyterephthalyl piperphenylamidine resin with concentrated sulfuric acid solid particles under sealing conditions, and using dry spray wet spinning method and multi-stage drying technology, the insufficient strength and modulus of para-aramid fibers are solved. Problem, high-strength and high-modulus fiber preparation is achieved, reducing production costs.

CN119145078APending Publication Date: 2024-12-17SHANDONG JUFANG NEW MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411576555.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing para-aramid fibers have low strength and modulus, making it difficult to meet high performance requirements.

Method used

Under sealing conditions, polyterephthalyl terephthalyl phenylenediamine resin with a water content of less than 500ppm was mixed with concentrated sulfuric acid solid particles, and the spinning raw liquid was prepared by dry spray wet spinning method, and it was dried in multiple stages to control the drying. The air layer height, draft ratio and solidification bath temperature during the wet spinning process can reduce the slurry sandwich phenomenon and polymer degradation, and improve the quality of the spinning raw liquid.

Benefits of technology

The strength and modulus of para-aramid fibers are significantly improved, high performance is maintained, drying time is shortened, and energy consumption and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention provides a para-aramid fiber and a preparation method thereof.Under the sealed condition, poly-p-phenylene terephthamide resin with the water content lower than 500 ppm and the viscosity of 6.5 dL / g-7. 5 dL / g and concentrated sulfuric acid solid particles are mixed, defoamed and filtered to obtain a spinning solution, then tows are obtained through a dry jet wet spinning method, and finally multi-stage drying is conducted to obtain the para-aramid fiber. The high-strength and high-modulus para-aramid fiber is obtained. The concentrated sulfuric acid solid particles are used as raw materials, the mixing and permeation effects of concentrated sulfuric acid on resin are enhanced, the slurry sandwich phenomenon is reduced, polymer degradation is relieved, a high-quality spinning solution is provided for preparing the high-strength and high-modulus aramid fiber, and the strength and modulus of the para-aramid fiber, especially the modulus, are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material synthesis, and in particular to a high-strength and high-modulus para-aramid fiber and a preparation method thereof. Background Art

[0002] The full name of para-aramid fiber is poly(p-phenylene terephthalamide) fiber. It is a high polymer obtained by polycondensation of p-phenylenediamine and terephthaloyl chloride. The high polymer is dissolved, extruded, and molded to obtain a high-performance special fiber. Para-aramid is a high-rigidity polymer with a high degree of symmetry and regularity in its molecular structure. Strong hydrogen bonds are formed between macromolecular chains. Therefore, it has the advantages of high strength, high modulus, high temperature resistance, low density, low heat shrinkage, and good dimensional stability. It is widely used in key fields such as aerospace, safety protection, information communication, transmission cables, and building structure reinforcement.

[0003] The prior art discloses a method for preparing para-aramid fiber, which generally involves dissolving a polymer resin in a sulfuric acid solution to form a spinning solution, and then spinning the para-aramid fiber to obtain the para-aramid fiber. However, the para-aramid fiber prepared by this method has low strength and modulus. Summary of the invention

[0004] In view of this, the present invention provides a high-strength and high-modulus para-aramid fiber and a preparation method thereof. The para-aramid fiber provided in the present application has higher strength and modulus.

[0005] The present application provides a method for preparing high-strength and high-modulus para-aramid fiber, comprising the following steps:

[0006] a) Under sealed conditions, poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g is mixed with concentrated sulfuric acid solid particles, and the spinning solution is obtained after degassing and filtering;

[0007] b) using the spinning solution obtained in step a) to obtain a filament bundle by dry-jet wet spinning;

[0008] c) performing multi-stage drying on the filament bundle to obtain high-strength and high-modulus para-aramid fiber.

[0009] In some specific implementations, the poly(p-phenylene terephthalamide) resin is prepared according to the following method:

[0010] Under the action of calcium chloride, p-phenylenediamine and terephthaloyl chloride are polymerized in N-methylpyrrolidone, and after washing and drying, poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g is obtained.

[0011] In some specific implementations, the water content of the poly(p-phenylene terephthalamide) resin is 100 ppm to 500 ppm.

[0012] In some specific implementations, the mass concentration of concentrated sulfuric acid in the concentrated sulfuric acid solid particles is 100±0.2%.

[0013] In some specific implementations, the mass concentration of the spinning solution is 15% to 25%.

[0014] In some specific implementations, the step b) specifically includes:

[0015] The spinning solution is ejected through the spinneret hole through the air layer, the obtained filament bundle is stretched and then enters the coagulation bath for coagulation and molding, and then washed and neutralized to obtain the filament bundle.

[0016] In some specific implementations, the thickness of the air layer is 1 mm to 10 mm;

[0017] The stretching ratio is 7 to 13;

[0018] The coagulation bath is water or sulfuric acid solution;

[0019] The temperature of the coagulation bath is 0°C to 10°C.

[0020] In some specific implementations, the step c) specifically includes:

[0021] The filament bundle obtained in step b) is washed, drained, and then subjected to first-stage drying and second-stage drying in sequence to obtain high-strength and high-modulus para-aramid fibers.

[0022] In some specific implementations, the temperature of the first stage drying is 90°C to 150°C, the time is 4s to 7s, and the moisture content of the tow is controlled to be 9% to 15%;

[0023] The temperature of the second stage drying is 300°C to 400°C, and the time is 1s to 1.5s.

[0024] In some specific implementations, the second stage drying is performed on a heated roller, and during drying, the fiber tension of the tow is 2 cN / dtex to 5 cN / dtex.

[0025] The present application also provides para-aramid fibers prepared by the method described in the above technical solution.

[0026] In this application, under sealed conditions, poly(p-phenylene terephthalamide) resin having a water content of less than 500ppm and a viscosity of 6.5dL / g~7.5dL / g is mixed with concentrated sulfuric acid solid particles, and a spinning solution is obtained after degassing and filtering, and then a dry-jet wet spinning method is used to obtain a tow, and finally multi-stage drying is performed to obtain a high-strength and high-modulus para-aramid fiber. This application uses concentrated sulfuric acid solid particles as raw materials, strengthens the mixing and penetration of concentrated sulfuric acid on the resin, reduces the slurry sandwich phenomenon, and also alleviates polymer degradation, providing high-quality spinning solution for the preparation of high-strength and high-modulus aramid fibers, greatly improving the strength and modulus of the para-aramid fibers, especially the modulus. Furthermore, this application maintains the high strength and high modulus properties of the para-aramid fibers by controlling parameters such as the air layer height, draft ratio, and coagulation bath temperature during dry-jet wet spinning, and does not deteriorate the properties. Moreover, the present application adopts graded drying to improve the drying efficiency of fiber moisture, shorten the drying time, reduce the structural defects of the fiber during the drying process, improve the fiber performance, reduce energy consumption, and reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic diagram of a typical preparation method provided in the embodiments of the present application. DETAILED DESCRIPTION

[0028] It should be understood that the expression "one or more of..." includes each of the items recited after the expression individually and in various different combinations of two or more of the recited items, unless otherwise understood from the context and usage. The expression "and / or" in combination with three or more recited items should be understood to have the same meaning, unless otherwise understood from the context.

[0029] The use of the terms "comprising", "having" or "containing", including their grammatical synonyms, should generally be understood as open and non-restrictive, for example not excluding other unrecited elements or steps, unless otherwise specifically stated or otherwise understood from the context.

[0030] It should be understood that the order of steps or the order in which certain actions are performed is not important as long as the present invention remains operable. In addition, two or more steps or actions may be performed simultaneously.

[0031] The use of any and all examples or exemplary language, such as "for example" or "including", herein is intended only to better illustrate the invention and does not limit the scope of the invention unless otherwise claimed. No language in this specification should be construed as indicating that any non-claimed element is essential to the practice of the invention.

[0032] In addition, the numerical ranges and parameters used to define the present invention are approximate values, and the relevant values ​​in the specific embodiments have been presented as accurately as possible. However, any numerical value inherently inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise expressly stated, it should be understood that all ranges, quantities, values ​​and percentages used in this disclosure are modified by "about". Here, "about" generally means that the actual value is within plus or minus 10%, 5%, 1% or 0.5% of a specific value or range.

[0033] The present application provides a method for preparing high-strength and high-modulus para-aramid fiber, comprising the following steps:

[0034] a) Under sealed conditions, poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g is mixed with concentrated sulfuric acid solid particles, and the spinning solution is obtained after degassing and filtering;

[0035] b) using the spinning solution obtained in step a) to obtain a filament bundle by dry-jet wet spinning;

[0036] c) performing multi-stage drying on the filament bundle to obtain high-strength and high-modulus para-aramid fiber.

[0037] The present application uses poly(p-phenylene terephthalamide) resin with a water content of less than 500ppm and a viscosity of 6.5dL / g~7.5dL / g as a raw material, and mixes it with concentrated sulfuric acid solid particles. The concentrated sulfuric acid solid particles strengthen the mixing and penetration effect of the concentrated sulfuric acid on the resin, reduce the slurry sandwich phenomenon, and also alleviate polymer degradation, thereby providing high-quality spinning solution for the preparation of high-strength and high-modulus aramid fibers.

[0038] In some specific implementations, the water content of the poly(p-phenylene terephthalamide) resin is less than 500 ppm, preferably 100 ppm to 500 ppm, and more preferably 200 ppm to 400 ppm. In some specific implementations, the viscosity of the poly(p-phenylene terephthalamide) resin is 6.5 dL / g to 7.5 dL / g, preferably 6.8 dL / g to 7.3 dL / g.

[0039] The present application has no special restrictions on the source of the poly(p-phenylene terephthalamide) resin, which can be purchased from the market or prepared according to the following method:

[0040] Under the action of calcium chloride, p-phenylenediamine and terephthaloyl chloride are polymerized in N-methylpyrrolidone, and after washing and drying, poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g is obtained.

[0041] The present application uses calcium chloride as a catalyst, N-methylpyrrolidone as a solvent, and p-phenylenediamine and terephthaloyl chloride as reaction raw materials to prepare a poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g.

[0042] In some specific implementations, the polymerization reaction is carried out under nitrogen protection. In some specific implementations, the molar ratio of p-phenylenediamine to terephthaloyl chloride is 1.001~1.002:1. In some specific implementations, the temperature of the polymerization reaction is 65~90°C, preferably 70°C~85°C, and the time of the polymerization reaction is 2min~5min, preferably 3min~4min. In some specific implementations, in the reaction system, the mass concentration of calcium chloride is 6.5%~8%, preferably 7%~7.5%; the molar concentrations of p-phenylenediamine and terephthaloyl chloride are independently 0.1mol / L~1mol / L, preferably 0.3 mol / L ~0.5mol / L.

[0043] Specifically, the present invention uses N-methylpyrrolidone / calcium chloride (NMP / CaCl 2 ) are respectively transported to the polymerization reactor by mass flow meter at a molar ratio of TPC to PPD of 1.001:1 to 1.002:1 for polymerization reaction.

[0044] After the polymerization reaction is completed, the obtained poly(p-phenylene terephthalamide) resin is washed and dried. The present application has no special restrictions on the washing and drying methods and parameters, and the washing and drying methods can be carried out according to methods well known to those skilled in the art.

[0045] The present application uses concentrated sulfuric acid solid particles as raw materials, strengthens the mixing and penetration of concentrated sulfuric acid on the resin, reduces the slurry sandwich phenomenon, and also alleviates polymer degradation, providing high-quality spinning solution for preparing high-strength and high-modulus aramid fibers. In some specific implementations, the mass concentration of concentrated sulfuric acid in the concentrated sulfuric acid solid particles is 100±0.2%.

[0046] In the present application, a poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g is mixed with concentrated sulfuric acid solid particles under a sealed condition, and a spinning solution is obtained after degassing and filtering. Specifically, in the present application, the poly(p-phenylene terephthalamide) resin and the concentrated sulfuric acid solid particles are stirred and mixed in a multi-stage partitioned jacket under a nitrogen sealed condition.

[0047] In some specific implementations, the temperature of the multi-stage partition jacket is 70°C to 100°C. Preferably, the multi-stage partition jacket is divided into 8 zones, and the temperatures are 70°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, and 100°C, respectively. The present application has no special restrictions on the dosage ratio of the poly(p-phenylene terephthalamide) resin and the concentrated sulfuric acid solid particles, so that the mass concentration of the spinning solution obtained after stirring, mixing, degassing and filtering is 15% to 25%. Preferably, the mass concentration of the spinning solution is 19% to 22%, more preferably 19.3% to 21.5%. The present application has no special restrictions on the methods and parameters of the degassing and filtration, and those skilled in the art can select according to their needs.

[0048] After the spinning solution is obtained, it is spun, preferably by dry-jet wet spinning to obtain a tow. Specifically, it includes the following steps:

[0049] The spinning solution is ejected through the spinneret hole through the air layer, the obtained filament bundle is stretched and then enters the coagulation bath for coagulation and molding, and then washed and neutralized to obtain the filament bundle.

[0050] The present application uses a gear pump to extrude the spinning solution from the spinneret. In some specific implementations, the spinneret has an aperture of 0.05 mm to 0.10 mm, preferably 0.065 mm, and the number of holes is 500 f to 2000 f, preferably 1000 f. The obtained filament bundle passes through the air layer. In some specific implementations, the thickness of the air layer is 1 mm to 10 mm, preferably 2 mm to 8 mm, and then the obtained filament bundle (i.e., the stock solution thin stream) is quickly stretched and then enters the coagulation bath for coagulation. In some specific implementations, the draft ratio of the stretching is 7 to 13, preferably 8 to 12. In some specific implementations, the coagulation bath is water or sulfuric acid solution. When it is a sulfuric acid solution, the concentration of sulfuric acid is 0.01% to 12%, preferably 1% to 10%, and more preferably 5% to 8%. In some specific implementations, the temperature of the coagulation bath is 0°C to 10°C, preferably 1°C to 8°C, and more preferably 2°C to 7°C.

[0051] The coagulated filament bundle is washed and neutralized to obtain a filament bundle. In some specific implementations, the washing is low-temperature washing, the temperature is -5 to 5°C, preferably -3°C to 3°C. In some specific implementations, alkali is used for neutralization, and the alkali includes but is not limited to sodium hydroxide, calcium hydroxide, calcium carbonate, etc., preferably sodium hydroxide.

[0052] The obtained tow is subjected to multi-stage drying to obtain high-strength and high-modulus para-aramid fiber. Specifically, the present application firstly washes the neutralized tow again, filtrates the water, and then sequentially performs the first-stage drying and the second-stage drying to obtain high-strength and high-modulus para-aramid fiber. In some specific implementations, the re-washing is high-temperature washing at a temperature of 50 to 80°C, preferably 60 to 70°C. The present application has no special restrictions on the washing and filtration methods and parameters, and those skilled in the art can select as needed.

[0053] After filtering the water, the obtained tow is subjected to a first stage drying. In some specific implementations, the temperature of the first stage drying is 90°C to 150°C, preferably 100°C to 140°C, the time is 4s to 7s, preferably 4.5s to 6.5s, and the moisture content of the tow is controlled to be 9% to 15%, preferably 10% to 14%. In some specific implementations, the first stage drying is performed in a hot oven.

[0054] After the first stage of drying is completed, the obtained filament bundle is subjected to a second stage of drying. In some specific implementations, the temperature of the second stage of drying is 300°C to 400°C, preferably 320°C to 380°C, and the time is 1s to 1.5s. In some specific implementations, the second stage of drying is carried out on a heating roller, and during drying, the fiber tension of the filament bundle is 2cN / dtex to 5cN / dtex. In some specific implementations, when the second stage of drying is carried out on a heating roller, the winding speed is 150m / min to 250m / min, preferably 180m / min to 230m / min.

[0055] After shaping, the obtained para-aramid fiber has a strength of 26 g / D~28 g / D and a modulus of 800 g / D~1000 g / D.

[0056] See also Figure 1 , Figure 1 A typical preparation method flow chart provided in the present application embodiment is as follows: first, under nitrogen protection, a solution of N-methylpyrrolidone / calcium chloride (NMP / CaCl 2 ) are transported to a one-step polymerization reactor by mass flow meters at a molar ratio of TPC to PPD of 1.001:1 to 1.002:1 for polymerization reaction. The obtained reaction product is washed and dried, mixed and dissolved with concentrated sulfuric acid solid particles, degassed and filtered, spun through a spinneret, and coagulated in a coagulation bath after drawing to obtain a tow. The tow is then washed with cold water, neutralized with sodium hydroxide, washed with hot water, filtered by a water filtration system, dried in a hot oven for the first time, and dried on a heating roller for the second time while being drawn to obtain para-aramid fiber. The fiber can be put into storage after oiling, winding, quality inspection, and packaging.

[0057] In this application, under sealed conditions, poly(p-phenylene terephthalamide) resin having a water content of less than 500ppm and a viscosity of 6.5dL / g~7.5dL / g is mixed with concentrated sulfuric acid solid particles, and a spinning solution is obtained after degassing and filtering, and then a dry-jet wet spinning method is used to obtain a tow, and finally multi-stage drying is performed to obtain a high-strength and high-modulus para-aramid fiber. This application uses concentrated sulfuric acid solid particles as raw materials, strengthens the mixing and penetration of concentrated sulfuric acid on the resin, reduces the slurry sandwich phenomenon, and also alleviates polymer degradation, providing high-quality spinning solution for the preparation of high-strength and high-modulus aramid fibers, greatly improving the strength and modulus of the para-aramid fibers, especially the modulus. Furthermore, this application maintains the high strength and high modulus properties of the para-aramid fibers by controlling parameters such as the air layer height, draft ratio, and coagulation bath temperature during dry-jet wet spinning, and does not deteriorate the properties. Moreover, the present application adopts graded drying to improve the drying efficiency of fiber moisture, shorten the drying time, reduce the structural defects of the fiber during the drying process, improve the fiber performance, reduce energy consumption, and reduce costs.

[0058] The high-strength and high-modulus para-aramid fiber and the preparation method thereof provided by the present application are further described below in conjunction with the embodiments.

[0059] Example 1

[0060] (1) Preparation of polymer: Under nitrogen protection, dissolve the polymer in N-methylpyrrolidone / calcium chloride (NMP / CaCl 2 ) were respectively transported to a polymerization reactor by mass flow meter at a molar ratio of TPC to PPD of 1.001:1 to 1.002:1, and polymerized at 65°C for 5 min. The obtained poly(p-phenylene terephthalamide) (PPTA) was washed and dried to obtain a PPTA resin with a water content of 100 ppm and a viscosity of 6.5 to 7.0 dL / g;

[0061] (2) Preparation of spinning solution: In a multi-stage partitioned jacket having 8 zones with temperatures of 70°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C and 100°C, respectively, the PPTA resin prepared in step (1) was mixed and stirred with solid particles of concentrated sulfuric acid having a concentration of 100±0.2% under nitrogen sealing, and then degassed and filtered to prepare a spinning solution having a mass concentration of 19.3%;

[0062] (3) Dry-jet wet spinning: The spinning solution prepared in step (2) is squeezed out from a spinneret (aperture 0.065 mm, number of holes 1000f) through a gear pump, and the filament bundle passes through a 4 mm air layer, and the thin stream of the solution is rapidly stretched at a draft ratio of 10, and enters a 0°C coagulation bath to be frozen and solidified. The coagulation bath is a sulfuric acid solution with a concentration of 8%. The obtained filament bundle is washed with 0°C low-temperature water, neutralized with sodium hydroxide to a pH of 6.5-7.0, and washed again with 50°C hot water. The water is filtered to obtain the filament bundle;

[0063] (4) Multi-stage drying technology: The filament bundle obtained in step (3) is dried in a hot oven at 90°C for 7 seconds, with the moisture content controlled at 15%, and then heat-set on a high-temperature heating roller at 300°C for 1.5 seconds. During the heat-setting process, the fiber tension is controlled within the range of 2 cN / dtex, and the winding speed is 150 m / min to obtain para-aramid fiber. The para-aramid fiber has a breaking strength of 26 g / D and a modulus of 800 g / D.

[0064] Example 2

[0065] (1) Preparation of polymer: Under nitrogen protection, dissolve the polymer in N-methylpyrrolidone / calcium chloride (NMP / CaCl 2 ) were respectively transported to a polymerization reactor by mass flow meter at a molar ratio of TPC to PPD of 1.001:1 to 1.002:1, and polymerized at 70°C for 4 min. The obtained poly(p-phenylene terephthalamide) (PPTA) was washed and dried to obtain a PPTA resin with a water content of 200 ppm and a viscosity of 6.5 to 7.0 dL / g;

[0066] (2) Preparation of spinning solution: In a multi-stage partitioned jacket having 8 zones with temperatures of 70°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C and 100°C, respectively, the PPTA resin prepared in step (1) was mixed with solid particles of concentrated sulfuric acid having a concentration of 100±0.2% under nitrogen sealing, and then degassed and filtered to prepare a spinning solution having a mass concentration of 20.1%;

[0067] (3) Dry-jet wet spinning: The spinning solution prepared in step (2) is squeezed out from a spinneret (aperture 0.065 mm, number of holes 1000f) through a gear pump, and the filament bundle passes through a 4 mm air layer, and the thin stream of the solution is rapidly stretched at a draft ratio of 8, and enters a 5°C coagulation bath to be frozen and solidified. The coagulation bath is a 9% sulfuric acid solution. The obtained filament bundle is washed with -5°C low-temperature water, neutralized with sodium hydroxide to a pH of 6.5-7.0, and washed again with 60°C hot water. The water is filtered to obtain the filament bundle;

[0068] (4) Multi-stage drying technology: The filament bundle obtained in step (3) is dried in a hot oven at 150°C for 4 seconds, with the moisture content controlled at 12%, and then heat-set on a high-temperature heating roller at 400°C for 1.5 seconds. During the heat-setting process, the fiber tension is controlled within the range of 5 cN / dtex, and the winding speed is 250 m / min to obtain para-aramid fiber. The para-aramid fiber has a breaking strength of 27 g / D and a modulus of 950 g / D.

[0069] Example 3

[0070] (1) Preparation of polymer: Under nitrogen protection, dissolve the polymer in N-methylpyrrolidone / calcium chloride (NMP / CaCl 2 ) were respectively transported to a polymerization reactor by mass flow meter at a molar ratio of TPC to PPD of 1.001:1 to 1.002:1, and polymerized at 75°C for 3 min. The obtained poly(p-phenylene terephthalamide) (PPTA) was washed and dried to obtain a PPTA resin with a water content of 500 ppm and a viscosity of 6.5 to 7.0 dL / g;

[0071] (2) Preparation of spinning solution: In a multi-stage partitioned jacket having 8 zones with temperatures of 70°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C and 100°C, respectively, the PPTA resin prepared in step (1) was mixed with solid particles of concentrated sulfuric acid having a concentration of 100±0.2% under nitrogen sealing, and then degassed and filtered to prepare a spinning solution having a mass concentration of 21.5%;

[0072] (3) Dry-jet wet spinning: The spinning solution prepared in step (2) is squeezed out from a spinneret (aperture 0.065 mm, number of holes 1000f) through a gear pump, and the filament bundle passes through a 7 mm air layer, and the thin stream of the solution is rapidly stretched at a draft ratio of 8, and enters a 10°C coagulation bath to be frozen and solidified. The coagulation bath is a 10% sulfuric acid solution. The obtained filament bundle is washed with 5°C low-temperature water, neutralized with sodium hydroxide to a pH of 6.5-7.0, and washed again with 70°C hot water. The water is filtered to obtain the filament bundle;

[0073] (4) Multi-stage drying technology: The filament bundle obtained in step (3) is dried in a hot oven at 150°C for 4 seconds, with the moisture content controlled at 9%, and then heat-set on a high-temperature heating roller at 350°C for 1 second. During the heat-setting process, the fiber tension is controlled within the range of 4 cN / dtex, and the winding speed is 150 m / min to obtain para-aramid fiber. The para-aramid fiber has a breaking strength of 28 g / D and a modulus of 1000 g / D.

[0074] Example 4

[0075] (1) Preparation of polymer: Under nitrogen protection, dissolve the polymer in N-methylpyrrolidone / calcium chloride (NMP / CaCl 2 ) were respectively transported to a polymerization reactor by mass flow meter at a molar ratio of TPC to PPD of 1.001:1 to 1.002:1, and polymerized at 80°C for 3 min. The obtained poly(p-phenylene terephthalamide) (PPTA) was washed and dried to obtain a PPTA resin with a water content of 400 ppm and a viscosity of 6.5 to 7.0 dL / g;

[0076] (2) Preparation of spinning solution: In a multi-stage partitioned jacket having 8 zones with temperatures of 70°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C and 100°C, respectively, the PPTA resin prepared in step (1) was mixed with solid particles of concentrated sulfuric acid having a concentration of 100±0.2% under nitrogen sealing, and then degassed and filtered to prepare a spinning solution having a mass concentration of 19.8%;

[0077] (3) Dry-jet wet spinning: The spinning solution prepared in step (2) is squeezed out from a spinneret (aperture 0.065 mm, number of holes 1000f) through a gear pump, and the filament bundle passes through a 7 mm air layer, and the thin stream of the solution is rapidly stretched at a draft ratio of 7, and enters a coagulation bath at 8°C to be frozen and solidified. The coagulation bath is a sulfuric acid solution with a concentration of 11%. The obtained filament bundle is washed with water at -2°C, neutralized with sodium hydroxide to a pH of 6.5-7.0, and washed again with hot water at 80°C. The water is filtered to obtain the filament bundle;

[0078] (4) Multi-stage drying technology: The filament bundle obtained in step (3) is dried in a hot oven at 100°C for 5 seconds, with the moisture content controlled at 10%, and then heat-set on a high-temperature heating roller at 300°C for 1.2 seconds. During the heat-setting process, the fiber tension is controlled within the range of 3 cN / dtex, and the winding speed is 150 m / min to obtain para-aramid fiber. The para-aramid fiber has a breaking strength of 27 g / D and a modulus of 900 g / D.

[0079] Example 5

[0080] (1) Preparation of polymer: Under nitrogen protection, dissolve the polymer in N-methylpyrrolidone / calcium chloride (NMP / CaCl 2) were respectively transported to a polymerization reactor by mass flow meter at a molar ratio of TPC to PPD of 1.001:1 to 1.002:1, and polymerized at 90°C for 2 min. The obtained poly(p-phenylene terephthalamide) (PPTA) was washed and dried to obtain a PPTA resin with a water content of 300 ppm and a viscosity of 6.5 to 7.0 dL / g;

[0081] (2) Preparation of spinning solution: In a multi-stage zoned jacket having 8 zones with temperatures of 70°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C and 100°C, respectively, the PPTA resin prepared in step (1) was mixed with solid particles of concentrated sulfuric acid having a concentration of 100±0.2% under nitrogen sealing, and then degassed and filtered to prepare a spinning solution having a mass concentration of 21.0%;

[0082] (3) Dry-jet wet spinning: The spinning solution prepared in step (2) is squeezed out from a spinneret (aperture 0.065 mm, number of holes 1000f) through a gear pump, and the filament bundle passes through a 5 mm air layer, and the thin stream of the solution is rapidly stretched at a draft ratio of 10, and enters a coagulation bath at 3°C ​​to be frozen and solidified. The coagulation bath is a sulfuric acid solution with a concentration of 12%. The obtained filament bundle is washed with low-temperature water at 2°C, neutralized with sodium hydroxide to a pH of 6.5-7.0, and washed again with hot water at 65°C, and the water is filtered to obtain a filament bundle;

[0083] (4) Multi-stage drying technology: The filament bundle obtained in step (3) is dried in a hot oven at 90°C for 6 seconds, with the moisture content controlled at 12%, and then heat-set on a high-temperature heating roller at 400°C for 1.3 seconds. During the heat-setting process, the fiber tension is controlled within the range of 5 cN / dtex, and the winding speed is 180 m / min to obtain para-aramid fiber. The para-aramid fiber has a breaking strength of 26 g / D and a modulus of 850 g / D.

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing high-strength and high-modulus para-aramid fiber, comprising the following steps: a) Under sealed conditions, poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g is mixed with concentrated sulfuric acid solid particles, and the spinning solution is obtained after degassing and filtering; b) using the spinning solution obtained in step a) to obtain a filament bundle by dry-jet wet spinning; c) performing multi-stage drying on the filament bundle to obtain high-strength and high-modulus para-aramid fiber.

2. The preparation method according to claim 1, characterized in that: The poly(p-phenylene terephthalamide) resin is prepared according to the following method: Under the action of calcium chloride, p-phenylenediamine and terephthaloyl chloride are polymerized in N-methylpyrrolidone, and after washing and drying, poly(p-phenylene terephthalamide) resin having a water content of less than 500 ppm and a viscosity of 6.5 dL / g to 7.5 dL / g is obtained.

3. The preparation method according to claim 1, characterized in that: The water content of the poly(p-phenylene terephthalamide) resin is 100ppm to 500ppm; The mass concentration of concentrated sulfuric acid in the concentrated sulfuric acid solid particles is 100±0.2%.

4. The preparation method according to claim 1, characterized in that: The mass concentration of the spinning solution is 15% to 25%.

5. The preparation method according to claim 1, characterized in that: The step b) specifically comprises: The spinning solution is ejected through the spinneret hole through the air layer, the obtained filament bundle is stretched and then enters the coagulation bath for coagulation and molding, and then washed and neutralized to obtain the filament bundle.

6. The preparation method according to claim 5, characterized in that: The thickness of the air layer is 1 mm to 10 mm; The stretching ratio is 7 to 13; The coagulation bath is water or sulfuric acid solution; The temperature of the coagulation bath is 0°C to 10°C.

7. The preparation method according to claim 1, characterized in that: The step c) specifically comprises: The filament bundle obtained in step b) is washed, drained, and then subjected to first-stage drying and second-stage drying in sequence to obtain high-strength and high-modulus para-aramid fibers.

8. The preparation method according to claim 7, characterized in that: The first stage drying temperature is 90°C to 150°C, the time is 4s to 7s, and the moisture content of the tow is controlled to be 9% to 15%; The temperature of the second stage drying is 300°C to 400°C, and the time is 1s to 1.5s.

9. The preparation method according to claim 8, characterized in that: The second stage drying is carried out on a heated roller, and during drying, the fiber tension of the tow is 2 cN / dtex to 5 cN / dtex.

10. Para-aramid fiber prepared by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Acid-resistant high-modulus para-aramid fiber and preparation method thereof

    CN120738784A

  • Method for preparing high-modulus para-aramid fiber by using benzoxazine coating containing functional particles

    CN121110372A